DESAIN ANTENA MIKROSTRIP RADAR CUACA PESAWAT PADA FREKUENSI 9,4 GHZ - Renata Salma Ramadhanty; Bambang Bagus Hariyanto; Teguh Imam Suharto (Journal of Public Transportation Community, 2023)
The application of radar in the world of aviation is the existence of aircraft weather radar to monitor weather conditions around the aircraft in real time. Aircraft weather radar requires an antenna to support detection. The author makes microstrip antenna design research using the Wilkinson Power Divider (WPD) method combined with array techniques to produce high gain parameters. The research method uses 4D from Thiagarajan, namely Define, Design, Develop and Disseminate. To obtain high gain, this study designs single patch, 1x2, 4x4, and 8x4 antenna designs with insert feed and coaxial integration techniques. Then compare based on the substrate used, namely FR-4 and Rogers RT-5880. Analysis includes gain, VSWR, return loss, bandwidth and radiation pattern. The microstrip design is made by doing antenna calculations and determining the method used, namely array and WPD, then designing the design in the application. The FR-4 and Rogers RT- 5880 substrate microstrip antenna design has a VSWR value <2 and return loss <- 10 dB. The highest gain on the 8 x 4 insert feed Rogers RT-5880 array was 17.979 dBi and the bandwidth with the highest value of the 1x2 Rogers RT-5880 array was 651.1 MHz. Gain increases proportional to the number of patches. The Rogers RT- 5880 material produces higher gain than FR-4.